Glycemic Threshold as an Alternative Method to Identify the Anaerobic Threshold in Patients With Type 2 Diabetes - Delevatti, Rodrigo S.; Kanitz, Ana Carolina; Alberton, Cristine L.; Marson, Elisa Corrêa; Pantoja, Patricia Dias; Pinho, Carolina DertzbocherFeil; Lisboa, Salime Chedid; Kruel, Luiz Fernando M. (Frontiers in Physiology, 2018)
Purpose: To analyze the agreement between the velocity, heart rate, and oxygen uptake values corresponding to second ventilatory threshold and glycemic threshold in patients with type 2 diabetes. Methods: Twenty-four untrained patients (55.1 ± 8.9 years) were evaluated. Three different parameters of training intensity corresponding to anaerobic threshold, one mechanical (velocity) and two physiological (heart rate and oxygen uptake) parameters, were identified by a classical method (second ventilatory threshold) and by an alternative method (glycemic threshold). To determine the threshold values, patients performed an incremental treadmill test, with an initial velocity of 3 km.h-1 for 3 min, that was then increased by 1 km.h-1 every 2 min. Comparisons between mean values and the degree of agreement between second ventilatory threshold and glycemic threshold were analyzed using the paired t-test and Bland-Altman test, respectively. Results: All patients performed the tests appropriately, and no adverse effects were recorded. Patients demonstrated similar mean velocity (p = 0.25), heart rate (p = 0.97) and oxygen uptake (p = 0.71) between the ventilatory threshold (6.4 ± 0.6 km.h-1, 130.1 ± 18.7 bpm, 15.2 ± 3.5 ml.kg.min-1) and the glycemic threshold (6.2 ± 0.9 km.h-1, 130.2 ± 12.8 bpm, 15.0 ± 3.8 ml.kg.min-1). Conclusions: The present study indicates an agreement between the glycemic and second ventilatory methods in determination of the anaerobic threshold of patients with type 2 diabetes; and thus, either method may be used for these patients.